ANALYSIS OF THE RELATIONSHIP BETWEEN INDIRECT COSTS, BID PRICES, AND TIME PERFORMED BY SMALL CONTRACTORS IN SIDOARJO REGENCY - Syaefuddin Zuhri; Budi Witjaksana; Hanie Teki Tjendani (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
In each construction project, there are numerous essential project parameters, with cost being identified as the most critical factor due to its direct or indirect implications on every decision made. Cost holds significant importance for contractors, especially small contractors, who must strive to submit competitive bid prices while ensuring good construction quality and optimal time management. Therefore, it is imperative for small contractors to carefully evaluate indirect cost expenditures in order to achieve minimal costs without compromising on quality or project duration. This research delves into the correlation between indirect costs, bid prices, and time performance among small contractors in Sidoarjo. The study involves primary data processing and employs analytical methods, including multiple linear regression statistical analysis. The findings suggest that both indirect costs and bid prices have a notable impact on project duration, accounting for 52.4% of the variance in time performance.